Mechanisms of Surface Antigenic Variation in the Human Pathogenic Fungus Pneumocystis jirovecii - Schmid-Siegert, Emanuel (mBio, 2017)
Microbial pathogens commonly escape the human immune system by varying surface proteins. We investigated the mechanisms used for that purpose by Pneumocystis jirovecii. This uncultivable fungus is an obligate pulmonary pathogen that in immunocompromised individuals causes pneumonia, a major life-threatening infection. Long-read PacBio sequencing was used to assemble a core of subtelomeres of a single P. jirovecii strain from a bronchoalveolar lavage fluid specimen from a single patient. A total of 113 genes encoding surface proteins were identified, including 28 pseudogenes. These genes formed a subtelomeric gene superfamily, which included five families encoding adhesive glycosylphosphatidylinositol (GPI)-anchored glycoproteins and one family encoding excreted glycoproteins. Numerical analyses suggested that diversification of the glycoproteins relies on mosaic genes created by ectopic recombination and occurs only within each family. DNA motifs suggested that all genes are expressed independently, except those of the family encoding the most abundant surface glycoproteins, which are subject to mutually exclusive expression. PCR analyses showed that exchange of the expressed gene of the latter family occurs frequently, possibly favored by the location of the genes proximal to the telomere because this allows concomitant telomere exchange. Our observations suggest that (i) the P. jirovecii cell surface is made of a complex mixture of different surface proteins, with a majority of a single isoform of the most abundant glycoprotein, (ii) genetic mosaicism within each family ensures variation of the glycoproteins, and (iii) the strategy of the fungus consists of the continuous production of new subpopulations composed of cells that are antigenically different.